Effects of regulation on youth unemploy-ment: evidence from European countries - Zubović, Jovan; Zdravković, Aleksandar; Pavlović, Dejana (Industrija, 2015)
Economic trends in recent years have led to rising unemployment across Europe. This trend is particularly evident among youth. At the same time, the negative demographic trends in many countries show that the number of young people is decreasing. Problems among young people are the reflection of the future state of the nation. Therefore there is a need to analyse whether the government can reduce youth unemployment rate using available regulatory tools. In this paper, the authors have analysed the impact of three groups of factors on the youth unemployment rate by using multiple regression analysis and controlling the long-term determinants of unemployment. The results show that the level of unemployment is largely impacted by a tax rate on low wages, primarily in the mid-term. Factors related to the general rate of unemployment, as well as the other demographic factors have showed no statistically significant impact on mid-term and long-term youth unemployment rate.
Keywords: Labour Market Regulations; Demographic Factors; Youth unemployment; Youth; Unemployment